Disturbance Observer Based Power Control of DFIG Under Unbalanced Network Conditions. Issue 13 (9th August 2018) - Ozsoy, Emre; Soner, Burak; Ahmad, Fiaz; Rasool, Akhtar; Sabanovic, Asif; Gokasan, Metin; Bogosyan, Seta; Sanjeevikumar, P.
Abstract: This article investigates a new current control strategy for grid connected doubly fed induction generators (DFIG) under unbalanced grid voltage conditions. DFIG dynamic model is represented in synchronously rotating symmetrical component dq frames of references. A proportional controller which feed forwards estimated disturbance terms is proposed for power control in unbalanced voltage conditions to accomplish positive sequence power demand and also to dissipate negative sequence components which cause double frequency oscillations in power. DFIG parameters are not required to be known since it estimates the machine parameters relevant nonlinear terms with a disturbance observer (DOB). The novel controller structure is implemented by using dSPACE ds1103 digital controller which controls a 1.1 kW DFIG experimental setup.